Akumulasi α-Tokoferol pada Organ Tanaman dan Kultur Suspensi Sel Jatropha gossypiifolia Dari Nusa Tenggara Timur - Meri Helsiana Mata (Fakultas Pertanian, Universitas Timor, 2021)
Jatropha gossypiifolia Linn. is a type of medicinal plant because it has bioactive compounds such as phenolic acids, flavonoids, saponins, tannins, alkaloids, coumarins, lignins, phenols, steroids, and terpenoids contained in leaves, bark, roots, seeds, fruit, and sap. In addition to these bioactive compounds, another bioactive compound was found, namely tocopherol which is known to have antioxidant activity and can be used to treat several diseases. This study aimed to measure α-tocopherol in plant organs and cell culture of J. gossypiifolia. Crumb callus was induced using Murashige and Skoog (MS) medium and Vitamin Gamborg with the addition of 1.35 x 10-5 2,4-Dichlorophenoxyacetate (2,4-D) and 4,4 x 10-6 M kinetin. Cell suspension cultures were produced by subculture of crumbled callus on MS medium with the addition of 1.35x10-5 2,4-D and 4.4 x 10-6 M kinetin and 30 g/L sucrose. Measurement of the content of -tocopherol seen in plant organs and culture age 0; 3; 6; 9; 12; 15; 18 days using High Performance Liquid Chromatography (HPLC) method using methanol:water (95:5) as mobile phase. The results showed that the callus formation of J. gossypiifolia was observed after the explants were incubated for one week. The content of α-tocopherol in cell suspension culture of J. gossypiifolia was detected at the beginning of the culture age and then decreased and increased again until the 9th day. The content of α-tocopherol on day 9 was 0.23%. After the 9th day, the α-tocopherol content began to decrease. In culture medium, α-tocopherol was also found since the beginning of culture and the percentage increased on the 9th day until it reached a maximum on the 12th day of 0.12%. The level of α-tocopherol in the plant organs of J. gossipiifolia was highest in the roots of 0.12%.